Agenda for the 70's : youth and national progress. [Sponsored by the Dept. of Psychology, Ateneo de Manila and the Cultural Affairs Office, U.S. Embassy. - Seminar for Student Leaders, 2d, Tagaytay, City, 1970 (Manila, 1970)
Cover title